ISLAMISASI ILMU DAN LANGKAH-LANGKAHNYA (KAJIAN EPISTIMOLOGI DAN METODOLOGI) - Azidni Rofiqo dan Abna Hanif Novel (Al-Intaj)
:  Islamization of science is a very important study, it appears in the middle of the Muslim community who lost their identity longer. The idea of Islamization of science was first raised by al-Faruqi when meeting The International Institute of Islamic Thought in Washington in 1981. The Islamization of science in this paper begins with the definition of science, followed by the characteristics of science, the process of knowledge, and the process of Islamization of science knowledge. The type of this research is descriptive qualitative research using primary data that is book written by Al Attas, Al Faruqi, and secondary data that is from book, journal, supporting article. The results of this discussion indicate that science comes from qouliyah and kauniyah verses. To save the Muslims from wersternisasi then the Islamization of science should be disseminated to the community, especially among the Muslim educated